The role of reservation services in tourism (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
A hotel reservation system is a software solution that enables business owners to automate the process of accepting and managing bookings. A good hotel booking system serves as a centralised platform that allows guests to make reservations for rooms, amenities, and services. Meanwhile, an online reservation system also provides hoteliers with a streamlined way to handle reservations, availability, pricing, and guest information.